Heterogeneous Catalysis for Lithium-Sulfur Batteries: Enhanced Rate Performance by Promoting Polysulfide Fragmentations - Jeong, Tae-Gyung; Choi, Dong Shin; Song, Hannah; Choi, Jihwan; Park, Shin-Ae; Oh, Si Hyoung; Kim, Heejin; Jung, Yousung; Kim, Yong-Tae (AMER CHEMICAL SOC, 2017)
A spatial confiment of polysulfides using the metal compound additives having polar surfaces has been considered to be a promising approach to address the insufficient rate capability and cyclability of lithium-sulfur batteries. Herein, we report a more effective approach outperforming this conventional one: a heterogeneous catalysis to promote polysulfide fragmentations. It was revealed using combined computational and experimental approaches that an ultrastrong adsorption of elemental sulfur on TiN surfaces resulted in a spontaenous fragmentation into shorter chains of polysulfides. This heterogeneous catalysis reaction improved the sluggish kinetics of polysulfide reduction because of the chemical disproportionation at the second plateau. A markedly enhanced rate capability was finally obtained, exhibiting a discharge capacity of 700 mAh g(-1) at a scan rate of 5C.